An Assessment of Risks Along the Sweet Potato Value Chain in Ghana - Wie, Prosper; Aidoo, Robert; Sorensen, Olav Jull (Asian Development Policy Review, 2017)
This study was aimed at examining risks and the various risk management strategies adopted by actors along the sweet potato value chain in Ghana by focusing on Fanteakwa (Southern sector) and West Mamprusi (Northern sector) districts. Data were collected from both primary and secondary sources. Selection of 200 producer respondents was done using the simple random sampling technique whilst a combination of accidental sampling and snowballing techniques were used to select 100 traders and 80 processors of sweet potato. Descriptive statistics were used to identify and analyze risks and management strategies employed by value chain actors. The Random Variability Index (RVI) was used to determine the level of predictability of the various risks. The study results revealed that, risks along the sweet potato value chain were seen to be identical along the chain with wide variations in predictability and management strategies employed by actors. All the levels of the sweet potato value chain identified sudden changes in output price as the most important risk. However, output level variability, market cost variability and variability in post-harvest (rotten) losses were the least predicted at the production, trader and processor levels of the chain respectively. Also, actors generally devised management strategies that mainly reduced the impact of these risks and ultimately maximize their utility. It is therefore recommended that actors should be encouraged to form associations and contract prices in advance since it is seen as being the best risk management tool for dealing with price risk especially when the said risk is seen to be the most important along the entire chain.